Impact of large-scale social restrictions on air quality (NO₂, CO, O₃) during COVID-19: Surabaya case study, Indonesia - Asmaul Nur Fitria; Supriyadi Supriyadi; Muhammad Al-Irsyad; Anindya Hapsari (Public Health and Occupational Safety Journal)
Background: The COVID-19 pandemic galvanized the world at the end of 2019. It was identified as an attack on humans and spread very quickly almost all over the world. As the person in charge of protecting the community, the government makes a policy that can suppress the spread of the COVID-19 virus.